Corporal punishment and adolescent aggression: An examination of multiple intervening mechanisms and the moderating effects of parental responsiveness and demandingness. (May 2021) - Liu, Weidi; Guo, Siying; Qiu, Geping; Zhang, Sheldon X.
Abstract: Background: Research on generational transmission of violence in general suggests that corporal punishment leads to children's aggressive behavior. However, less clear is the intervening mechanisms that link corporal punishment with adolescent aggression and the moderation on the intervening mechanisms. Objectives: This study examined the mediating role of negative emotions, endorsement of violence, and low self-control in the association between parental corporal punishment and adolescent aggression and investigated whether the intervening mechanisms operated differently according to different levels of parental responsiveness and demandingness. Participants and setting: Data from a sample (N = 1, 635) of students in central China were used. The students were from 4 schools, aged between 12–18. Methods: Conditional process analysis was performed to assess the moderated mediation. Results: The relations of corporal punishment with adolescent aggression were partially mediated by adolescent's endorsement of violence (b = .027, p < .001), negative emotion (b = .028, p < .001), and low self-control (b = .008, p = .007). In addition, these indirect effects were moderated by parental responsiveness and demandingness. Conclusion: Our study adds further empirical credence in our collective effort to reduce adolescent aggressive behavior by banning corporal punishment as a disciplinary practice. Further, parenting programs by social welfare agencies should consider the important role of demandingness. Interventions could reduce adolescent aggression also by adolescent resilience development, improving one's self-control and management of negative emotion while cultivating moral beliefs disapprove of violence.